Lithium-Ion Batteries - Thin Film for Energy Materials and Devices 2020
DOI: 10.5772/intechopen.90032
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Analysis of Solid-Electrolyte Interphase Layer on Germanium Thin Films and the Effect of Vinylene Carbonate Electrolyte Additive

Abstract: Germanium thin-film anodes for Li-ion battery applications are the focus of the present work. As part of this chapter, we shall briefly review the use of germanium thin films in Li-ion batteries, and subsequently, new results pertaining to the effect of vinylene carbonate (VC) as electrolyte additive on the electrochemical performance are presented. We have used cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy to investigate the performance. Thin-film electrode perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…XPS also indicated the formation of germanium carbide in the Ge–Al electrode during cycling, but not in the Ge–Cu electrode. Germanium carbide has been shown previously to develop in Ge Li-ion anodes during cycling and indicates side reactions of germanium with the electrolyte solvents or the carbon black conductive additive during cycling. Raman spectroscopy showed a lesser degree of pulverization of the germanium in the Ge–Al electrode during cycling compared to the Ge–Cu electrode.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…XPS also indicated the formation of germanium carbide in the Ge–Al electrode during cycling, but not in the Ge–Cu electrode. Germanium carbide has been shown previously to develop in Ge Li-ion anodes during cycling and indicates side reactions of germanium with the electrolyte solvents or the carbon black conductive additive during cycling. Raman spectroscopy showed a lesser degree of pulverization of the germanium in the Ge–Al electrode during cycling compared to the Ge–Cu electrode.…”
Section: Resultsmentioning
confidence: 95%
“…However, predictive calculations show that for a 18650 format Li-ion cell the achievable specific energy and energy density are very similar to those achievable with current graphite-on-copper anodes. With use of advanced conductive additives such as carbon nanotubes, , as well as SEI-forming electrolyte additives that have been studied with germanium anodes like vinylene carbonate , or fluoroethylene carbonate, ,, the composite electrical percolation and conductivity can be increased, the germanium mass fraction in the composite can be increased, and stability of the SEI can be further improved. Altogether, such improvements can further increase the achievable cell specific energy and energy density as well as lead to an anode with the necessary performance stability for Li-ion cells with long cycle life.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate formation of the SEI through electrolyte modification is a promising strategy to address this issue. , Previous studies have evaluated the effectiveness of electrolyte additives such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC) , on the SEI. These reports show an advantageous additive effect on long-term cycling, through introduction of fluorinated species. Previous reports have noted the synergy between the Si morphology and electrolyte additives to achieve extended cyclability with more than 2000 mAh g –1 over 50 cycles, where the use of FEC leads to surface film compositions leading to lower impedance throughout (de)­lithiation …”
Section: Introductionmentioning
confidence: 82%
“…For bulk Si, electrolyte additives such as fluoroethylene carbonate (FEC), vinylene carbonate, and propylene carbonate have improved long‐term cyclability through their reduction or stabilization of surface fluorinated species. [ 21–23 ] Specifically, the improved cycle life of cells utilizing FEC as an electrolyte additive has been attributed to the formation of a more homogenous and robust SEI. [ 24 ] It has also been demonstrated that FEC leads to superior surface film compositions causing an overall lower impedance.…”
Section: Introductionmentioning
confidence: 99%